The Three Stooges : Ebenezer Stooge - Gladir, George (Three Stooges (Papercutz (Firm)), 2012)
The Three Stooges become entangled in the crazy schemes of a mad scientist in "Ebenezer Stooge." Then they take on a giant, the three bears, and a little Red Riding Hood's grandma in "Thrice Upon a Time."